HISTORY OF TRANSFORMATION OF THE DAGESTAN FESTIVAL IGBY - Kapustina, Ekaterina Leonidovna (History, Archeology and Ethnography of the Caucasus, 2021)
The paper reviews the history of one of the unique traditional festivals of Mountainous Dagestan – Igby, the midwinter festival. The festival, which was celebrated in only three villages of the Tsuntinsky district – Shailti, Kituri, and Geniyatli, – was first described during the scientific research in 1983, conducted by the prominent ethnologist-caucasiologist Yu.Yu. Karpov. The paper considers the main vectors of transformation of the festival in 1980s-1990s: the inclusion of new characters and elements of the scenario, inter-village competitions, self-presentation of a village through the festival. The study highlights discussions in jamaats regarding the overestimation of the significance of the festival under the influence of re-Islamization of the region, which ultimately led to conflict situations and the prohibition of the holiday in all villages that previously celebrated it, by 2007. At the same time, having discontinued in the mountain villages of the Tsuntinsky district, the festival has found its new life in the virtual space due to the emergence of papers and videos on the Internet about it, as well as with the inclusion of Igby in the register of Russia’s intangible cultural heritage. As a result, Igby can be defined as a “quasi-local” festival: virtual and bureaucratic events associated with Igby emphasize its unique locality, but at the same time they are held without interaction with the locality itself – the villages of the Tsuntinsky District. The once real festival of several rural societies, having faded away in the mountains, nevertheless continues to live, has turned into a republican cultural project, losing not only connection with the original location and thus receiving a “common Dagestani nature”, but also separating from its local prototype and getting a new page in history. The research has been conducted with use of case study method. The study is based on field material, collected by the author during the work in the Tsuntinsky district and Makhachkala in Summer of 2021; on various data from the Internet, material sources and photo-collections of Kuntskamera, related to the festival.